Dose-dependent hemato-biochemical and genotoxic responses of common carp (Cyprinus carpio) to flupyradifurone - Yıldırım, Önder; Acar, Ümit; Tezel, Rifat; Erden, Yavuz; Bilge, Gökçen; Yapıcı, Sercan (Frontiers in Physiology, 2025)
Flupyradifurone (FPF), a systemic butenolide insecticide introduced in 2014, is increasingly used as an alternative to neonicotinoids, yet its safety for non-target aquatic organisms remains poorly understood. This study evaluated the acute and sub-lethal toxicity of FPF in juvenile common carp (Cyprinus carpio). A 96-h static bioassay determined an LC50 of 140.47 mg/L. Fish were then exposed for 14 days to sub-lethal concentrations (1, 3, 5, 25, 75 and 125 mg/L) to assess hematological, biochemical, and genotoxic responses. Hematological analysis revealed significant, dose-dependent declines in red blood cells (1.71 × 106/μL in control vs. 1.12 × 106/μL at 125 mg/L), hemoglobin (8.34 vs. 3.34 g/dL), and hematocrit (26.08% vs. 13.73%), accompanied by reduced mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration at higher doses, indicating anemia and impaired oxygen transport. Biochemically, glucose increased sharply (102.21 mmol/L in control to 230.29 mmol/L at 125 mg/L), while triglycerides, cholesterol, total protein, and albumin declined significantly, suggesting metabolic disruption. Hepatic enzyme activities (alkaline phosphatase, serum glutamic oxaloacetic transaminase, serum glutamate pyruvate transaminase) increased markedly, with serum glutamic oxaloacetic transaminase rising from 36.47 U/L in controls to 144.02 U/L at 125 mg/L, indicative of hepatocellular damage. Comet assay confirmed pronounced DNA damage at ≥25 mg/L, with significant elevations in tail length, tail moment, and % DNA in tail. Collectively, these results demonstrate that FPF exposure compromises hematological health, disrupts metabolic balance, and induces genotoxicity in common carp, even at sub-lethal concentrations. Incorporating both physiological and genomic endpoints is essential for comprehensive ecological risk assessments of emerging insecticides.